Um ensino de eletrostática planejado construtivamente para o 9º ano - Ramos, Willian Miguel Pereira (2015)
The current situation of the Brazilian science education is not good, given that whenever a story is conveyed in educational journals such as the Journal School (2014) faced with a distant reality of the reality of some countries in view our performance in the final round of PISA (2006) verified that the discipline of natural sciences. Generally the teaching of natural sciences is confused with teaching just biology, and forgotten the areas of astronomy, physics and chemistry, as we find ourselves PCNEF (2012). In this work we rescued a teaching and learning theory that revolutionized the American education in the 60 Teaching by discovering Jerome Bruner and his proposal of a curriculum spiral format, where each content is proposed superficially and deeper according to the student learning, we will seek that the student becomes the center of each classroom and that exists in each class not only spectators, but builders of knowledge through teaching by discovery. The SOLO taxonomy (Structure Of The Observed Learning Outcome) provide in each class a constructive alignment between the expected learning outcomes, the method and the resources used for teaching and verification of what has been learned through short quizzes, having a reinforcement of content throughout the process of teaching and learning. When in the classroom we apply grounded in the SOLO taxonomy scripts that will be divided into 50-minute lessons presented to students the principles of electrification and the electrification processes: friction, contact and induction. Each activity will be developed individually or in motivating staff always seeking the student build their own knowledge having with guiding the teacher in the classroom. However it is essential that the reader does not understand this project as savior of physical education for elementary schools, as there are some research in this educational line, of course not on the constructive planning, for example, (Terrimar Ignacio Pasqualetto, 2011), as well other methods can be used, but it is clear that the constructive alignment and teaching by discovery are very good teaching strategies when applied in physics teaching.